"Open to the public": Keeping interiors publicly accessible in the context of counter-terrorism guidelines. (18th March 2020) - Kimmel, Laurence; Barnard, Mike; Kuru, Aysu
Abstract : Purpose: The cultural imperative for public buildings in countries like Australia to maintain their intrinsic "openness" – physically and symbolically – faces particular challenges in the context of current global terrorism concerns. Building regulations and counter-terrorism guidelines coexist uneasily, with implications for both public amenity and safety. This is particularly evident in the context of current approaches to hostile vehicle (HV) mitigation. Design/methodology/approach: Based on a review of comparative literature, this multidisciplinary project assimilates design aesthetics and security expertise to assess the advantages and limitations of current counter-terrorism design approaches in Australia, the UK and the USA. The research focusses on public buildings of high cultural symbolic value (e.g. concert halls) in the context of HV mitigation. Findings: Two key recommendations emerge. The first presents the benefits of adopting a layered security strategy tailored to a building's security and symbolic profile mix. The second proposes enhancements to the existing counter-terrorism guidelines based on a model that accounts for both symbolic value and openness. Originality/value: The research presents new strategies for urban design and security stakeholders to balance openness and security in the design of publicly accessible buildings. While existing research addresses the challenges of terrorism in the design of public space, a literature (and practice) gap exists in Australia, the UK and the USA regarding current approaches to the design of public buildings. Using Australia as a case study, the findings will inform government and industry practitioners seeking more complementary approaches to public amenity and safety in comparable counter-security design contexts globally.